Tilt‐induced biases in sediment trap functioning. Issue 12 (28th December 2015) - Chiswell, Stephen M.; Nodder, Scott D.
Abstract: We present data from two sediment traps moored 5 km apart ∼150 km off the east coast of New Zealand. Both traps were at 1500 m in 3100 m of water. One trap was attached to a 3038 m tall mooring and exhibited tilts measured by a tilt sensor ranging from 5° to 20°, the other trap was attached to a 1659 m tall mooring and exhibited tilts ranging from 2° to 4°. The computed relative trapping efficiency depends on which flux constituent (mass, particulate organic carbon, biogenic silica, etc.) is used to compute it. We suggest that this physically unrealistic result arises because of relatively high noise in the measurements due to patchiness, sampling and/or measurement errors. On average, the trap exhibiting most tilt collected 30–50% less material than the trap exhibiting least tilt. For the total mass flux, efficiencies appear to be lower at higher trap tilt. However, with only 5 months of data, we do not have enough samples to accurately model the relationship between trap tilt and efficiency, except to show that with even moderate tilt, the sediment trap trapping efficiency can be reduced by a factor of nearly two. Key Points: Two conical sediment traps were moored in close proximity off the east coast of New Zealand Particle fluxes from the taller mooring were significantly less than from the shorter mooring We conclude that trapping efficiency decreases with increasing trap tilt, even at moderate tilts